Clinical Profile among Febrile Patients Admitted With Thrombocytopenia in a Tertiary Care Hospital in Northern India - Piyush Kumar Gupta; Dr Smita Gupta; Dr Neeraj Kapoor, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Febrile thrombocytopenia is a common and challenging clinical presentation encountered particularly in tropical regions, often requiring prompt evaluation and management. In the last decade, parts of Asia have been witnessing an epidemic of severe fever with thrombocytopenia, and it has a high case-fatality rate. Therefore, a well-organized systemic approach, carried out with an awareness of causes of fever with thrombocytopenia can shorten the duration of investigations and bring out the diagnosis. Aim and Objectives: To evaluate the clinical profile among febrile patients presenting with thrombocytopenia and study the associated etiological factors and outcome in our setup. Material and Methods: A cross-sectional observational study conducted in the Department of General Medicine, Shri Ram Murti Smarak Institute of Medical Sciences, Bareilly on patients presenting with fever and diagnosed with thrombocytopenia during the period from July 2023 to December 2023. The clinical and laboratory parameters were studied and their outcomes were observed. Observations: 152 patients with febrile thrombocytopenia with mean age 58.57  3.77 years and were analysed dengue (43.42%) was found to be the major culprit and platelet count below 10,000 /μL, was observed among 88.89% cases from dengue. The most common bleeding manifestation observed was melena, accounting for 41.76% cases. Conclusion: Increased awareness and early recognition of thrombocytopenia can avoid catastrophes like fatal bleed and thus reduce morbidity and mortality.